PERKEMBANGAN PEMIKIRAN MANAJEMEN DARI GERAKAN PEMIKIRAN SCIENTIFIC MANAGEMENT HINGGA ERA MODERN - Baskara, I Gde Kajeng (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 7 Nomor 2 Tahun 2013)
This study is an overview of the various ideas related to concepts and techniques of management from the industrial revolution to the modern era. In this article the various theory or thought are classified into four areas. The classification is not based on the periodicity of the year, but more to the realm of thought being developed. The four areas are (1)scientific & administrative management theory, (2)behavioral management theory, (3)quantitative management theory and (4)modern  management theory. The field thought is presented by the emergence of the field earlier than other areas of thought, though the period or era of the movement of thought one area may also appear a work that is part of another movement of thought. The results of  this literature review shows that the development of management thought started from mechanical related t hinking and productivity in manufacturing, and then progressed to studies related to nature and human behavi or and proceed to the field of relationship between human and organization systems. This study also found a lack of attention from management historians that focuses on marketing or customer orientation.
Keywords: evolution thought, scientific management, modern management